Agglorative point: creating an urban lobby for Jeppestown - Valentim, Rafaela Sara (My University, 2017)
AGGLOMERATIVE POINT explores the themes of the arrival point, access and Right to the City, and movement. Located in Jeppestown, this document interprets the research with reference to the site of the existing Jeppe Train Station. The railway line severs the urban environment of East and West Jeppe, creating a juxtaposition of the physical and social context. The social, economic and political landscape is scattered along its urban environment, creating a complex and layered tapestry. This site is an important point in the arrival city, as it is the point at which the train stops and connects the commuters to the greater network of transport nodes in Jeppestown and the city. The commuters are celebrated and the movement patterns around the station are enhanced. At this point, an alternative nexus is created, where movement and rights intersect, based on new spatial arrangements altering how information is accessed and exchanged. The architectural response is an extension of the existing Jeppe Train Station and spans over a portion of the railway line. It is a transport hub that incorporates civic functions for information access and exchange. It renovates and enhances the commuter station and provides a platform for communication between the authority and community members. It is a landmark gateway that celebrates the entrance and arrival into Jeppestown. The design reconnects Fox Street across the railway line to stitch East and West Jeppe, creating an urban lobby for Jeppestown and an alternative point of intersection. “Architecture can’t force people to connect, it can only plan the crossing points, remove barriers, and make the meeting places useful and attractive” (Denise Scott Brown).
This document is submitted in partial fulfillment for the degree: Master of Architecture (Professional) at the University of the Witwatersrand, Johannesburg, South Africa, 2017